2012
DOI: 10.5812/jjm.4830
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Bacterial Strains Isolated From Urinary Tract Infections in Karaj, Iran

Abstract: The article will help Clinicians in predicting and planning correct strategies for UTI therapy.Backgrounds: Urinary Tract Infection (UTI) is one of the most common bacterial diseases worldwidethat can be presented asymptomatic or symptomatic, characterized by a wide range of symptoms from mild irritative voiding to bacteremia, sepsis, or even death. In latter decades, widespread utilization of antibiotics has resulted in increased incidence of antibiotic resistance among urinary tract pathogens all over the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
45
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 21 publications
21
45
2
2
Order By: Relevance
“…E. coli isolates, the predominant cause of UTIs, showed high resistance to gentamicin (73.69%). These isolates, the predominant cause of UTIs, showed high resistance to Gentamicin, Ampicillin and Cephalothin, and higher sensitivity to imipenem, Ciprofloxacin, Nitrofurantoin, and Ceftizoxime (22). The difference between this study and the present study was that in the current study was found to be most susceptible to Ciprofloxacin (59.3%).…”
Section: Discussioncontrasting
confidence: 81%
“…E. coli isolates, the predominant cause of UTIs, showed high resistance to gentamicin (73.69%). These isolates, the predominant cause of UTIs, showed high resistance to Gentamicin, Ampicillin and Cephalothin, and higher sensitivity to imipenem, Ciprofloxacin, Nitrofurantoin, and Ceftizoxime (22). The difference between this study and the present study was that in the current study was found to be most susceptible to Ciprofloxacin (59.3%).…”
Section: Discussioncontrasting
confidence: 81%
“…In this study from 460 positive urine cultures, 67.4% belonged to girls. Because the majority of reports were the same, we can conclude that short urethra, anatomic position of urinary system and rapid bacterial transfer to the upper part of the urinary system increases the risk of UTI in girls (4,5).…”
Section: Discussionmentioning
confidence: 85%
“…However, in another study nitrofurantoin and ceftriaxone were the most effective agents against E. coli in Iran (central diagnostic lab of Karaj) (4,5,24). In Nigeria, gentamicin was the most effective antibiotic against E. coli (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations